The presentation of self in the age of ChatGPT - Klowait, Nils; Erofeeva, Maria (Frontiers in Sociology)
Contemporary debates about artificial intelligence (AI) still treat automation as a straightforward substitution of human labor by machines. Drawing on Goffman’s dramaturgical sociology, this paper reframes AI in the workplace as supplementary rather than substitutive automation. We argue that the central—but routinely overlooked—terrain of struggle is symbolic-interactional: workers continuously stage, conceal, and re-negotiate what counts as “real” work and professional competence. Large language models (LLMs) such as ChatGPT exemplify this dynamic. They quietly take over the invisible, routinised tasks that underpin cognitive occupations (editing, summarizing, first-draft production) while leaving humans to enact the highly visible or relational facets that sustain occupational prestige. Drawing on diverse sources to illustrate our theoretical argument, we show how individual workers, dramaturgical teams, and entire professional fields manage impressions of expertise in order to counter status threats, renegotiate fees, or obscure the extent of AI assistance. The paper itself, having been intentionally written with the ‘aid’ of all presently available frontier AI models, serves as a meta-reflexive performance of professional self-staging. The dramaturgical framework clarifies why utopian tales of friction-free augmentation and dystopian narratives of total displacement both misread how automation is actually unfolding. By foregrounding visibility, obfuscation, and impression management, the article presents a differentiated case for AI’s impact on the performative structure of work, outlines diagnostic tools for assessing real-world AI exposure beyond hype-driven headlines, and argues for a more human-centered basis for evaluating policy responses to the ‘fourth industrial revolution.’ In short, AI enters the labor process not as an autonomous actor, but as a prop within an ongoing social performance—one whose scripts, stages, and audiences remain irreducibly human.

Leveraging VR Tools for Inclusive Education: Implications from Sign Language Learning in VRChat - Erofeeva, Maria; Klowait, Nils; Belov, Mikael; Soulié, Yoann (Communications in Computer and Information Science)

Challenges of lightweight design, vehicles, and rescuers - Hanses, Hendrik; Akbulut Irmak, Emine Fulya; Horwath, Ilona; Tröster, Thomas (Climate Protection, Resource Efficiency, and Sustainable Engineering. Transdisciplinary Approaches to Design and Manufacturing Technology)

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Development of operational and demand-oriented firefighting equipment - Hanses, Hendrik; Horwath, Ilona (Materials Today: Proceedings)
Keywords: General Medicine

(De)Coding Social Practice in the Field of XAI: Towards a Co-constructive Framework of Explanations and Understanding Between Lay Users and Algorithmic Systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Algorithmen, KI und soziale Diskriminierung - Horwath, Ilona (Inter- und multidisziplinäre Perspektiven der Geschlechterforschung)

Waschen, Warten, Wege ebnen. Ambivalente Fürsorge und der männliche Heldenmythos in der Feuerwehr - Horwath, Ilona; Kastein, Mara; Finke, Josefine (Care-Arbeit und Gender in der digitalen Transformation)

OPERATIONAL AND DEMAND-ORIENTED FIREFIGHTING EQUIPMENT - Hanses, Hendrik; Horwath, Ilona (Conference proceedings 38th Danubia Adria Symposium on Advances in Experimental Mechanics)

Advanced Automotive Components by Fiber-Metal-Laminates - Triebus, Marcel; Ostermann, Moritz; Tröster, Thomas; Horwath, Ilona (Materials in Car Body Engineering - Bad Nauheim)

Репликация эффектов интерактивного решения задач спичечной алгебры - Spiridonov, Vladimir; Erofeeva, Maria; Klowait, Nils; Ardislamov, Vladlen; Morozov, Maksim; Zdilar, Stevo (Психологические исследования)
Один из многообещающих вариантов внедрения моторной активности в процесс решения мыслительных задач был предложен в статье Weller и коллег. В ходе «интерактивного» условия эксперимента испытуемые могли взаимодействовать с реальными предметами, составлявшими проблемную ситуацию. Эта экспериментальная манипуляция привела к значимому увеличению успешности решения большинства использованных задач спичечной алгебры. С учетом того, что задачи различались по источникам сложности, трудно предложить один (или общий) вариант движений решателя, который мог бы объяснить одинаковое положительное влияние интерактивного условия на успешность решения задач разнойстепени сложности. Чтобы удостовериться в точности полученных результатов и оценить перспективность подобной экспериментальной манипуляции, мы провели концептуальную репликацию названного исследования в трех экспериментальных сериях, нацеленных: 1) напроверку эффектов интерактивного условия, 2) на расширенную репликацию тех же эффектов, поскольку она включала в себя экспериментальные условия, предполагающие разную степень моторной активности решателя, 3)на расширенную репликацию тех же эффектов, так как она содержала условия с максимально выраженной интерактивностью, благодаря использованию технологий виртуальной реальности. Кроме того, мы увеличили список зависимых переменных: помимо успешности решения было использовано количество эпистемических и прагматических действийрешателя. Увеличение количества первых может свидетельствовать о переносе части когнитивных функций на окружающую предметную среду. Ни в одном случае мы не смогли реплицировать результаты коллег. Хотя во второй серии эксперимента эпистемических действий было значимо больше, это никак не повлияло на успешность решения. Обсуждаются потенциал и проблемы интерактивного решения и его роль для изучения воплощенного познания.

Репликация эффектов интерактивного решения задач спичечной алгебры - Spiridonov, Vladimir; Erofeeva, Maria; Klowait, Nils; Ardislamov, Vladlen; Morozov, Maksim; Zdilar, Stevo (Психологические исследования)
Один из многообещающих вариантов внедрения моторной активности в процесс решения мыслительных задач был предложен в статье Weller и коллег. В ходе «интерактивного» условия эксперимента испытуемые могли взаимодействовать с реальными предметами, составлявшими проблемную ситуацию. Эта экспериментальная манипуляция привела к значимому увеличению успешности решения большинства использованных задач спичечной алгебры. С учетом того, что задачи различались по источникам сложности, трудно предложить один (или общий) вариант движений решателя, который мог бы объяснить одинаковое положительное влияние интерактивного условия на успешность решения задач разнойстепени сложности. Чтобы удостовериться в точности полученных результатов и оценить перспективность подобной экспериментальной манипуляции, мы провели концептуальную репликацию названного исследования в трех экспериментальных сериях, нацеленных: 1) напроверку эффектов интерактивного условия, 2) на расширенную репликацию тех же эффектов, поскольку она включала в себя экспериментальные условия, предполагающие разную степень моторной активности решателя, 3)на расширенную репликацию тех же эффектов, так как она содержала условия с максимально выраженной интерактивностью, благодаря использованию технологий виртуальной реальности. Кроме того, мы увеличили список зависимых переменных: помимо успешности решения было использовано количество эпистемических и прагматических действийрешателя. Увеличение количества первых может свидетельствовать о переносе части когнитивных функций на окружающую предметную среду. Ни в одном случае мы не смогли реплицировать результаты коллег. Хотя во второй серии эксперимента эпистемических действий было значимо больше, это никак не повлияло на успешность решения. Обсуждаются потенциал и проблемы интерактивного решения и его роль для изучения воплощенного познания.

Florian braucht Mehmet mehr als umgekehrt: Herausforderungen und Potenziale für Inklusion in der Freiwilligen Feuerwehr - Kastein, Mara; Finke, Josefine; Horwath, Ilona (Voluntaris)

Ohne den ‚Weissen Mann‘ würden Leute wie Sie noch in Erdhöhlen wohnen.“ - Die Markierung der Unmarkierten (Erscheinungsformen, Erklärungsversuche und Gegenstrategien, GENDER)

Feuerwehren im Spiegel gesellschaftlicher Diversität - Horwath, Ilona; Kastein, Mara; Duglar Sezer, Nilgün (Feuerwehren im Spiegel gesellschaftlicher Diversität)

Das schwankende Schiff der Männerpolitik: eine Metaphernanalyse - Kastein, Mara (Forum Qualitative Sozialforschung)
In dem Artikel werden die Metaphern gleichstellungsorientierter Männerpolitik als eine Form diskursiver Praktiken untersucht. In meiner Dissertation habe ich die Metaphernanalyse ergänzend zur Grounded-Theory-Methodologie und zur wissenssoziologischen Diskursanalyse genutzt, um die Ergebnisse zu verdichten und zu vertiefen. Dabei stellt die Metaphorik der gleichstellungsorientierten Männerpolitik selbige als instabil, schwankend, balancierend und uneinig dar, denn sie wird als schwankendes Schiff, welches ohne feste Route auf dem Meer schaukelt, imaginiert. Das Meer ist die Gesellschaft bzw. die übergeordnete Gleichstellungspolitik. Diese wird als unberechenbar und launisch konzipiert, und die gleichstellungsorientierte Männerpolitik erscheint dabei als ausgeliefert.

International Perspectives about COVID-19, Digital Labour and Gender Work Pattern: A Collective Interview (Gender a výzkum / Gender and Research)

A Plea to Reflect on the Entanglements of Gendered Work Patterns and Digital Technologies (Gender a výzkum / Gender and Research)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Chapter 5: Quantitative methodological approaches to citizenship and migration - Malancu, Natalia; Florea, Alexandra (Handbook of Citizenship and Migration)